A review on the effect of residual stresses in incremental sheet metal forming used in automotive and medical sectors. (2023) - Kajal, Gianender; Tyagi, M.R.; Kumar, Gulshan
Abstract: Incremental sheet forming (ISF) is a process that can produce sheet metal components with a series of stepwise small incremental deformation. This literature paper presents a thorough review of analyzing the influence of residual stresses in correlation with different process variables like tool diameter, tool path, the thickness of the sheet, depth of cut and wall angle, etc., during the procedure of single point incremental forming used in the automotive and medical industry. Moreover, this paper clearly explains the process parameters, which further help improve the ISF process compared to other conventional metal forming processes. This review initiates with the introduction of ISF for different types of materials and follows the residual stress measurement in various sectors. This paper also provides specific insights into the impact of residual stresses on forming forces, geometric shape accuracy, formability, and other factors in the process. The gap from this intensive review will provide the groundwork for the investigators for future research to recognize the implication of residual stresses in the automotive and medical fields. Based on the investigation, residual stresses should be considered in the design step of the manufacturing process with diverse scales. Finally, the future scope and probable research directions were discussed.